FRI0116 Pharmacokinetic Results from a Phase 1, Single-Centre, Double-Blind, Randomised, Single-Dose, Parallel Group Study Comparing 5 MG/KG IV Infusion of BOW015 and Reference Infliximab in Healthy Male Volunteers. (9th June 2015) - Lambert, J.; Wyand, M.; Lassen, C.; Shneyer, L.; Thomson, E.; Kay, J.
Abstract : Background: BOW015 is an IgG1 monoclonal antibody that binds to TNFα, which is being developed as a biosimilar to reference infliximab (rIFX, Remicade®). Preclinical studies demonstrate statistically significant dose-dependent suppression of synovitis in a murine transgenic arthritis model, with BOW015 and rIFX treatment each producing similar inhibition of joint inflammation. This clinical trial is the first-in-human study of BOW015. Objectives: To compare the pharmacokinetics (PK), safety and immunogenicity of BOW015 to rIFX in healthy Caucasian male volunteers. Methods: Eighty-four subjects were randomised to receive BOW015 or rIFX. A single 5 mg/kg IV infusion was administered over 2 hours to 43 subjects in the BOW015 group and 41 subjects in the rIFX group in a hospital-based clinical research unit. Subjects were discharged 2 days after the infusion and returned the next day for follow-up and then at 1, 2, 3, 5, 7, 9, and 12 weeks after the infusion. The treatments were compared using analysis of covariance for the PK parameters Cmax, AUC(0-t), and AUC(0-inf) . The criterion for PK bioequivalence was that the 90% confidence intervals (CIs) for the geometric mean ratios were contained within the range 0.80 to 1.25. Results: Study subjects ranged in age from 18 to 45 years with body weight between 60 to 90 kg and body mass index between 19 and 27 kg/m 2 . Geometric mean Cmax was 142.47 μg/mL following BOW015 infusion and 126.74 μg/mL following rIFX infusion. Geometric mean AUC(0-t) was 36, 211 h.μg/mL and 34, 304 h.μg/mL, and geometric mean AUC(0-inf) was 36, 775 and 34, 801 h.μg/mL following BOW015 and rIFX infusions, respectively. Bioequivalence was demonstrated, with 90% CIs for the treatment mean ratios of 1.07 to 1.18 for Cmax, 0.98 to 1.14 for AUC(0-t), and 0.98 to 1.15 for AUC(0-inf) . Apparent terminal phase half-life was similar for BOW015 (307.96 hours) and rIFX (280.22 hours). The range and median of time to peak concentration (tmax ) was also similar for BOW015 (range: 2.00–8.00 hours) and rIFX (range: 2.00–12.02 hours). The median tmax for BOW015 (3.97 hours) and for rIFX (2.05 hours) was not clinically significant and may have resulted from the 2-hour interval between samples and relatively slow drug elimination. Twenty six subjects (60.5%) in the BOW015 group reported 50 treatment-emergent adverse events (TEAEs) and 27 subjects (65.9%) in the rIFX group reported 54 TEAEs. No TEAE resulted in withdrawal from the study. At Week 12, 2 subjects in the rIFX group developed a positive QuantiFERON®-TB Gold test result, both of which were reported as a TEAE. No significant differences in immunogenicity were observed between the two treatment groups, with anti-drug antibodies [ADA]) developing in 8 subjects (18.6%) in the BOW015 group and in 10 subjects (24.4%) in the rIFX group by Week 12. Conclusions: PK biosimilarity was demonstrated for BOW015 and rIFX. Both treatments were considered to be well-tolerated, with similar safety profiles and no significant difference in the proportion of subjects developing ADA. Taken in combination with efficacy data, these results establish biosimilarity between BOW015 and rIFX. Acknowledgements: This research was sponsored by EPIRUS Biopharmaceuticals Inc. Disclosure of Interest: J. Lambert: None declared, M. Wyand Employee of: Epirus Biopharmaceuticals Inc., C. Lassen Employee of: Epirus Biopharmaceuticals Inc., L. Shneyer Shareholder of: Merck, E. Thomson Consultant for: Epirus Biopharmaceuticals, J. Kay Grant/research support from: AbbVie Inc.; Eli Lilly and Company; Pfizer Inc.; Roche Laboratories, Inc. (paid to the University of Massachusetts Medical School), Consultant for: Amgen, Inc.; AbbVie Inc.; AstraZeneca; Boehringer Ingelheim GmbH; Bristol-Myers Squibb Company; Eli Lilly and Company; Epirus Biopharmaceuticals Inc.; Genentech Inc.; Hospira, Inc.; Janssen Biotech, Inc.; Merck Sharp & Dohme Corp.; Nippon Kayaku Co., Ltd.; Novartis Pharmaceuticals Corporation; Pfizer Inc.; Samsung Bioepis; Roche Laboratories, Inc.; UCB, Inc.